Omega-3 intake is associated with liver disease protection - Vell, Mara Sophie; Creasy, Kate Townsend; Scorletti, Eleonora; Seeling, Katharina Sophie; Hehl, Leonida; Rendel, Miriam Daphne; Schneider, Kai Markus; Schneider, Carolin Victoria (Frontiers in Public Health, 2023)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) and alcoholic liver disease are among the most common liver diseases worldwide, and there are currently no Food and Drug Administration (FDA)-approved treatments. Recent studies have focused on lifestyle changes to prevent and treat NAFLD. Omega-3 supplementation is associated with improved outcomes in patients with chronic liver disease. However, it is unclear whether Omega-3 supplementation can prevent the development of liver disease, particularly in individuals at an increased (genetic) risk. Methods In this UK Biobank cohort study, we established a multivariate cox proportional hazards model for the risk of incident liver disease during an 11 year follow up time. We adjusted the model for diabetes, prevalent cardiovascular disorders, socioeconomic status, diet, alcohol consumption, physical activity, medication intake (insulin, biguanides, statins and aspirin), and baseline characteristics. Results Omega-3 supplementation reduced the risk of incident liver disease (HR=0.716; 95% CI: 0.639, 0.802; p=7.6x10-9). This protective association was particularly evident for alcoholic liver disease (HR=0.559; 95% CI: 0.347, 0.833; p=4.3x10-3), liver failure (HR=0.548; 95% CI: 0.343, 0.875; p=1.2x10-2), and non-alcoholic liver disease (HR=0.784; 95% CI: 0.650, 0.944; p=1.0x10-2). Interestingly, we were able to replicate the association with reduced risk of NAFLD in a subset with liver MRIs (HR=0.846; 95% CI: 0.777, 0.921; p=1.1x10-4). In particular, women benefited from Omega-3 supplementation as well as heterozygous allele carriers of the liver-damaging variant PNPLA3 rs738409. Conclusions Omega-3 supplementation may reduce the incidence of liver disease. Our study highlights the potential of personalized treatment strategies for individuals at risk of metabolic liver disease. Further evaluation in clinical trials is warranted before Omega-3 can be recommended for the prevention of liver disease.